Strengthening effectiveness evaluations to improve programs for women, children and adolescents. (30th June 2022) - Amouzou, Agbessi; Bryce, Jennifer; Walker, Neff; ,
ABSTRACT: A full understanding of the pathways from efficacious interventions to population impact requires rigorous effectiveness evaluations conducted under realistic scale-up conditions at country level. In this paper, we introduce a deductive framework that underpins effectiveness evaluations. This framework forms the theoretical and conceptual basis for the 'Real Accountability: Data Analysis for Results' (RADAR) project, intended to address gaps in guidance and tools for the evaluation of projects being implemented at scale to reduce mortality among women and children. These gaps include needs for a framework to guide decisions about evaluations and practical measurement tools, as well as increased capacity in evaluation practice among donors and program planners at global, national and project levels. RADAR aimed to improve the evidence base for program and policy decisions in reproductive, maternal, newborn and child health and nutrition (RMNCH&N). We focus on five linked methodological steps – presented as core evaluation questions – for designing and implementing effectiveness evaluation of large-scale programs that support both the needs of program managers to improve their programs and the needs of donors to meet their accountability responsibilities. RADAR has operationalized each step with a tool to facilitate its application. We also describe cross-cutting methodological issues and broader contextual factors that affect the planning and implementation of such evaluations. We conclude with proposals for how the global RMNCH&N community can support rigorous program evaluations and make better use of the resulting evidence.